Cooperative Planning, Uncertainty, and Managerial Control in Concurrent Design - Mitchell, Victoria L.; Nault, Barrie R. (Management Science, 2007)
We examine whether cooperative planning and uncertainty affect the magnitude of rework in concurrent engineering projects with upstream and downstream operations, and explore the impact of such rework on project delays. Using survey data from a sample of 120 business process (BP) redesign and related information technology (IT) development projects in healthcare and telecommunications, our results indicate that upstream (BP) rework and downstream (IT) rework is mediated and mitigated by cooperative planning through upstream/downstream strategy coupling and cross-functional involvement. In addition, uncertainty related to a lack of firm or industry experience with such projects increases the magnitude of upstream rework but not downstream rework or the amount of cooperative planning. After accounting for project scope, implementation horizon and whether delays are anticipated, we find that project delay is primarily influenced by the magnitude of downstream rework and downstream delay: the magnitude of both upstream and downstream rework significantly increases downstream delay, which significantly increases project delay. However, the magnitude of upstream rework does not directly affect project delay. These results suggest that project delay is under managerial control as cooperative planning is a managerial function that reduces downstream rework, while uncertainty from a lack of experience with the design affecting upstream rework is not directly under managerial control.